Surveillance of the Quality of Water for Human Consumption (VIGIAGUA) and fluoridation of the Public Supply Network: Monitoring in a municipality in the Southern Region of Brazil (Research, Society and Development, 2021)
Fluoridation of public water supply is considered one of the most effective systemic methods for preventing caries, with population coverage and good cost-benefit. In order for the maximum benefit of adding fluoride to the water supply occurs, it is necessary that the supply is constant and the concentration is within the range considered safe and ideal, which is done through external control. The objective of this study was to describe and analyze the action of Environmental Health Surveillance National Program related to the Water Quality for Human Consumption (VIGIAGUA), in relation to the control of the concentration of fluoride present in the public water supply in the municipality of Piraquara, Brazil, in 2018. The data were extracted from the Drinking Water Quality Surveillance Information System (SISAGUA), classified according to three criteria I (Brasil, 1975), II (Ramires et al., 2006) and III (Cecol/USP, 2011) and analyzed using  SPSS (version 20.0, IBM, EUA). Fourty-four analyzes were found, with an annual average of 0.622 mg F/L and standard deviation of 0.250. For criteria I and II the samples were classified as subfluoride and for criterion III it presented maximum benefit and minimum risk. The municipality did not comply with the National Guideline of the Sampling Plan for the Monitoring of Water Quality for Human Consumption and did not present continuous fluoride levels, indicating the need for adaptation. The strengthening of external control is necessary so that the anti-fluoridation discourse is not strengthened, putting at risk the advances achieved with this measure.